ChemInform Abstract: Rhodium‐Catalyzed Transannulation of N‐Sulfonyl‐1, 2, 3‐triazoles and Epoxides: Regioselective Synthesis of Substituted 3, 4‐Dihydro‐2H‐1, 4‐oxazines. Issue 10 (March 2015) - Ma, Xueji; Pan, Shanfei; Wang, Hangxiang; Chen, Wanzhi
Abstract Rh‐catalyzed reaction of 1, 2, 3‐triazoles with epoxides offers a short pathway to the synthesis of 3, 4‐dihydro‐2H‐1, 4‐oxazines (III), (VI), and (VIII) in moderate yields.